Sustainable Enterprise Value Creation Implementing Stakeholder Capitalism through Full ESG Integration - Samans, Richard; Nelson, Jane (Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
"While commitment to the principles of stakeholder capitalism is growing, the practice of them is still developing. ...That is what makes this book such an important contribution. It is the most extensive treatment to date of the practice and diverse legal and historical traditions of stakeholder capitalism, and it outlines an implementation framework for companies in any industry or country through their corporate governance, strategy, reporting and partnerships. As such, it fills a gap in both scholarship and practice." -From the Foreword by Klaus Schwab, Founder and Executive Chairman, World Economic Forum "An essential read for all current and future business leaders. We need to redirect capitalism to accelerate global systems transformations to deliver an equitable, net-zero and nature positive world. Jane and Rick expertly take leaders through the practical steps they must take to ensure their businesses continue to create long-term value for all their stakeholders. I look forward to seeing these principles and practices becoming the norm across the corporate world." -Peter Bakker, President and CEO, World Business Council for Sustainable Development "An insightful and timely book. Stakeholder capitalism can no longer be only a choice but rather must become the floor of competitive practice. A just, inclusive and sustainable future is possible but it will take major reform of investment and corporate practice. All investment must be governed with an ESG lens. And companies must accept responsibility for due diligence for human and labour rights with environmental standards as well as governance with an accountability that embeds these practices in the business model; the human centred approach so ably laid out here. A must read!" -Sharan Burrow, General Secretary, International Trade Union Confederation "Stakeholder capitalism is about adding value to all stakeholders, as this important book explains in great depth. We need to depart from the assumption that it is zero sum game. Technological advancements have made it possible to serve all stakeholders simultaneously, and it has become good business to develop sustainable solutions for the future. As such, ESG has become core to the strategy of any company, and transparency on ESG has become as important as the traditional financial reporting. Business leadership in this new era is about setting ambitious targets and over-delivering on both to create a sustainable future faster." -Jim Hagemann Snabe, Chairman of Siemens and A.P. Moller-Maersk, Vice Chairman, Allianz.